1979
DOI: 10.1161/01.cir.60.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced ST elevation in patients without myocardial infarction.

Abstract: SUMMARY A review of 6040 consecutive exercise tests yielded 106 patients without previous myocardial infarction (MI) who had exercise-induced ST elevation (. 0.5 mm in a 15-lead ECG system). In 46, ST elevation was correlated with left ventriculography and coronary angiography. Coronary artery disease (CAD) (> 70% narrowing) was detected in 40 of 46 patients: 12 patients had one-vessel disease, 13 had two-vessel disease, and 15 had three-vessel disease. Resting ventriculograms were normal in 36 of 40 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 39 publications
2
16
0
1
Order By: Relevance
“…1 On the other hand, the appearance of exercise-induced ST-segment elevation, although significantly less frequent than ST depression, seems to indicate a particular myocardial region, with ischemia either by coronary spasm or by severe narrowing of the coronary vessels in patients without prior myocardial infarction. [2][3][4][5][6][7] Consequently, the estimation of ST elevation in particular leads might be useful for identifying ischemic my-ocardial regions during exercise testing. Progress in this field appears to be promising, as reported recently by two studies, in which the value of ST elevation in the "pseudo-intracavitary" lead aVR and in lead V 1 was appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…1 On the other hand, the appearance of exercise-induced ST-segment elevation, although significantly less frequent than ST depression, seems to indicate a particular myocardial region, with ischemia either by coronary spasm or by severe narrowing of the coronary vessels in patients without prior myocardial infarction. [2][3][4][5][6][7] Consequently, the estimation of ST elevation in particular leads might be useful for identifying ischemic my-ocardial regions during exercise testing. Progress in this field appears to be promising, as reported recently by two studies, in which the value of ST elevation in the "pseudo-intracavitary" lead aVR and in lead V 1 was appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…However, persistent STsegment elevation is sometimes observed in patients with ventricular aneurysm, 3 and exercise or dobutamine stressinduced ST-segment elevation has been observed after MI, possibly due to ventricular asynergy. 4,5 Thus, it is important to determine whether myocardial ischemia is present in these patients. The present results showed that nonischemic ST-segment elevation was induced by regional ventricular dyskinesia, indicating that regional wall motion abnormalities can cause ST-segment elevation in the absence of coronary stenotic lesions and that ST-segment elevation is not always a good marker of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, an exercise or dobutamine stress-test sometimes induces ST-segment elevation in patients with an old anteroseptal MI, probably due to asynergy. 4,5 These findings suggest that regional ventricular dyskinesia is a possible mechanism for ST-segment elevation unrelated to myocardial ischemia.We investigated the role of regional ventricular dyskinesia in ST-segment elevation not associated with ischemia in a canine model of regional ventricular dyskinesia produced with negative inotropic agents. …”
mentioning
confidence: 91%
“…After the recording of baseline measurements (control), the coronary bypass was occluded again for 5 min followed by 15 Regional transmural ischemia causes both ST-segment elevation and systolic elongation (bulging) of the myocardium. Mechanical stretch might alter the transmembrane potentioal via stretch-activated ion channels (SAC); however, the role of SAC on ischemic ST-segment elevation has not yet fully studied.…”
Section: Experimental Preparationsmentioning
confidence: 99%